COVID‐19‐associated collapsing glomerulopathy: a report of two cases and literature review. Issue 12 (22nd December 2020) - Izzedine, Hassan; Brocheriou, Isabelle; Arzouk, Nadia; Seilhean, Danielle; Couvert, Philippe; Cluzel, Philippe; Pha, Micheline; Le Monnier, Ophelie; Varnous, Shadia; Andreelli, Fabrizio; Amoura, Zahir; Mathian, Alexis
Abstract: Nephrotic range proteinuria has been reported during the course of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) and coronavirus disease (COVID‐19). However, the pathological mechanisms underlying this manifestation are unknown. In this article, we present two cases of collapsing glomerulopathy (CG) associated with acute tubular necrosis during the course of COVID‐19, and review the literature for similar reports. In our two cases, as in the 14 cases reported so far, the patients were of African ancestry. The 14 patients assessed had an APOL1 high‐risk genotype. At the end of the reported period, two patients had died and five patients were still requiring dialysis. The 16 cases detailed in the present report strongly argue in favour of a causal link between SARS‐CoV‐2 infection and the occurrence of CG in patients homozygous for APOL1 high‐risk genotype for which the term COVID‐associated nephropathy (COVIDAN) can be put forward.